Expression of human β-N-acetylhexosaminidase B in yeast eases the search for selective inhibitors - Krejzová, Jana; Kulik, Natallia; Slámová, Kristýna; Křen, Vladimír (Enzyme and microbial technology, 2016)
Human lysosomal β-N-acetylhexosaminidases from the family 20 of glycoside hydrolases are dimeric enzymes catalysing the cleavage of terminal β-N-acetylglucosamine and β-N-acetylgalactosamine residues from a broad spectrum of glycoconjugates. Here, we present a facile, robust, and cost-effective extracellular expression of human β-N-acetylhexosaminidase B in Pichia pastoris KM71H strain. The prepared Hex B was purified in a single step with 33% yield obtaining 10mg of the pure enzyme per 1L of the culture media. The enzyme was used in the inhibition assays with the known mechanism-based inhibitor NAG-thiazoline and a wide variety of its derivatives in the search for specific inhibitors of the human GH20 β-N-acetylhexosaminidases over the human GH84 β-N-acetylglucosaminidase, which was expressed, purified and used in the inhibition experiments as well. Moreover, enzyme-inhibitor complexes were analysed employing computational tools in order to reveal the structural basis of the results of the inhibition assays, showing the importance of water-mediated interactions between the enzyme and respective ligands. The presented method for the heterologous expression of human Hex B is robust, it significantly reduces the costs and equipment demands in comparison to the expression in mammalian cell lines. This will enhance accessibility of this human enzyme to the broad scientific community and may speed up the research of specific inhibitors of this physiologically important glycosidase family.
Keywords: beta-Hexosaminidase beta Chain; exprese genu; Gene Expression; Recombinant Proteins; Kinetics; Hex B; Pichia pastoris; O-GlcNAcase; Enzyme Inhibitors; Enzyme inhibition; Thiazoles; molekulární modely; rekombinantní proteiny; Models, Molecular; acetylglukosamin; thiazoly; kinetika; β-N-acetylhexosaminidase; lidé; beta-hexosaminidasa, beta řetězec; Catalytic Domain; Humans; Acetylglucosamine; inhibitory enzymů; Pichia; katalytická doména